2018
DOI: 10.1039/c8dt01200h
|View full text |Cite
|
Sign up to set email alerts
|

Selective formation of formamidines, carbodiimides and formimidates from isocyanide complexes of Mn(i) mediated by Ag2O

Abstract: The isocyanide ligands in complexes fac-[Mn(CNR)(bipy)(CO)3]+ are selectively transformed into formamidines, carbodiimides and formimidates upon nucleophilic addition of NH2Me or alkoxides and subsequent treatment with Ag2O, which promotes tautomerization or oxidation processes of the former carbene ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…On the contrary, protic diaminocarbene complexes are very stable [16,17] and, as shown in the present case, can be transformed into the corresponding formamidine complexes by addition of a catalyst (Scheme 1). Interestingly, we have similarly demonstrated that coordinated NHCs isomerize to imidazoles under the same conditions [13,14]. In order to shed light on the mechanism of this intriguing reaction and to make a contribution to the rather scarcely developed field of mechanistic studies of organic and organometallic transformations assisted by Ag 2 O, we have now carried out DFT theoretical calculations supporting the finding that the exclusive behavior of Ag 2 O in the catalytic isomerization of diaminocarbenes to formamidines is essentially based on an ideal combination of the basic character of the oxide ion and the Lewis acid character of the Ag + ion.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…On the contrary, protic diaminocarbene complexes are very stable [16,17] and, as shown in the present case, can be transformed into the corresponding formamidine complexes by addition of a catalyst (Scheme 1). Interestingly, we have similarly demonstrated that coordinated NHCs isomerize to imidazoles under the same conditions [13,14]. In order to shed light on the mechanism of this intriguing reaction and to make a contribution to the rather scarcely developed field of mechanistic studies of organic and organometallic transformations assisted by Ag 2 O, we have now carried out DFT theoretical calculations supporting the finding that the exclusive behavior of Ag 2 O in the catalytic isomerization of diaminocarbenes to formamidines is essentially based on an ideal combination of the basic character of the oxide ion and the Lewis acid character of the Ag + ion.…”
Section: Introductionmentioning
confidence: 73%
“…The detailed experimental procedure for the synthesis and spectroscopic structural characterization (FTIR and NMR) of 1, 2, and 3 complexes has been described previously [13,14]. Selected crystallographic data and structure refinement parameters for 3•ClO − 4 are given here for the first time in Table S1 of the Supplementary Material, while Figure 1 shows the experimental molecular structure together with the atomic numbering scheme and selected bond lengths and angles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These ligands were then used as carbene transfer agents (see section 6.4). More recently, they published a report on the reversible tautomerization of this type of complexes mediated by Ag 2 O [51].…”
Section: Mixed Nhc/bipyridine Complexesmentioning
confidence: 99%
“…They also showed that the same procedure does not work for the synthesis of silver(I) complexes. More recently, this tautomerization phenomenon has been used by Ruiz and co-workers to transform isocyanides into diaminocarbenes, formamidines, carbodiimides, alkoxyaminocarbenes and formimidates [51].…”
Section: Tautomerizationmentioning
confidence: 99%